2007
DOI: 10.1016/s0377-1237(07)80101-8
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Bronchoscopy in the Evaluation of Mediastinal and Hilar Lymphadenopathy

Abstract: Background : The diagnosis in cases of mediastinal and/or hilar lymphadenopathy with no lung parenchymal involvement is often difficult. We undertook this study to assess the diagnostic value of flexible bronchoscopy (FOB) especially transbronchial needle aspiration (TBNA) and transbronchial lung biopsy (TBLB) in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The neoplastic causes include lymphoma, leukaemia and metastatic carcinoma. Sarcoidosis is also a common cause of intra thoracic lymphadenopathy [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The neoplastic causes include lymphoma, leukaemia and metastatic carcinoma. Sarcoidosis is also a common cause of intra thoracic lymphadenopathy [2].…”
Section: Discussionmentioning
confidence: 99%
“…Also Rai et al [2] mentioned that bronchoscopy showed abnormality in 39.6% of patients with mediastinal lymphadenopathy and these abnormalities included widening of main carina in 12.5%, widening of secondary carina in 8.3%, bulge into airways because of extrinsic compression in 14.6% and endobronchial nodule in 4.2% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While metastatic cancer, lymphoma and sarcoidosis are more common causes of lymphadenopathy in the developed world, infective and benign aetiologies are more likely in the developing world like India. 1,2 Mediastinal lymphadenopathy requires accurate diagnosis to determine the optimal treatment. For this nodal sampling is necessary that has traditionally been done by CT-guided fine needle aspiration cytology (FNAC) and/or biopsy, mediastinoscopy, and/or thoracoscopy.…”
Section: Introductionmentioning
confidence: 99%